Effectiveness of Discovery Based Learning Model in Improving Al-Qur’an Hadis Learning Outcomes on Mad Lazim Material in MTs DDI Seppange - St. Nur Alam; St. Jumaeda; Eka Kartini (al-Iltizam: Jurnal Pendidikan Agama Islam, 2026)
This study investigates the effectiveness of the Discovery Based Learning (DBL) model in elevating student achievement in Al-Qur'an Hadis, specifically on the topic of Mad Lazim, among ninth-grade students of MTs DDI Seppange during the academic year 2022/2023. The persistently low learning outcomes recorded in the pre-cycle phase an average score of 77.4 with a mastery rate of merely 37% provided the primary impetus for this classroom action research. Employing a two-cycle spiral design adapted from the Kemmis and McTaggart framework, each cycle was structured around the sequential phases of planning, action, observation, and reflection. Data were gathered through cognitive post-tests administered at the conclusion of each cycle and through structured observation sheets used to monitor student engagement and learning behavior. Quantitative descriptive statistics were applied to analyze all collected data. The results reveal a consistent and statistically meaningful improvement: the class average rose from 77.4 in the pre-cycle to 82.0 in Cycle I accompanied by an 88% mastery rate and further to 85.4 in Cycle II, at which point all 32 students attained full mastery (100%). These findings confirm that the DBL model, by positioning students as active inquirers who construct knowledge through guided exploration, constitutes an educationally sound and contextually applicable strategy for improving Al-Qur'an Hadis learning outcomes at the MTs level.